2017
DOI: 10.7759/cureus.1769
|View full text |Cite
|
Sign up to set email alerts
|

Intraprostatic Fiducials Compared with Bony Anatomy and Skin Marks for Image-Guided Radiation Therapy of Prostate Cancer

Abstract: PurposeProstate motion occurs during radiotherapy for localized prostate cancer. We evaluated the input of intraprostatic fiducials for image-guided radiation therapy and compared it with bony anatomy and skin marks.MethodsEleven patients were implanted with three fiducial markers in the prostate. Daily sets of orthogonal kV-kV images were compared with digitally reconstructed radiography. Data were recorded for skin marks, bony anatomy, and fiducial markers. The variations were analyzed along three principal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example, in the prostate, a CyberKnife fiducial tracking study showed intrafraction fiducial array COM shifts that ranged up to 10.00 mm (mean 2.61 mm) with RBE <1.50 mm (when using a clinical threshold of COM ~5.00 mm) [14]. Other prostate radiotherapy studies have reported inter and intrafraction organ points-of-interest, inter-fiducial COM, inter-fiducial distance variations, and single fiducial displacements of 5.0-18.0 mm during some patient treatments [9,12,15-18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the prostate, a CyberKnife fiducial tracking study showed intrafraction fiducial array COM shifts that ranged up to 10.00 mm (mean 2.61 mm) with RBE <1.50 mm (when using a clinical threshold of COM ~5.00 mm) [14]. Other prostate radiotherapy studies have reported inter and intrafraction organ points-of-interest, inter-fiducial COM, inter-fiducial distance variations, and single fiducial displacements of 5.0-18.0 mm during some patient treatments [9,12,15-18].…”
Section: Introductionmentioning
confidence: 99%